Advanced reactor engineering with 3D printing for the continuous-flow synthesis of silver nanoparticles - Okafor, Obinna; Weilhard, Andreas; Fernandes, Jesum A.; Karjalainen, Erno; Goodridge, Ruth; Sans, Victor (Royal Society of Chemistry, 2017)
The implementation of advanced reactor engineering concepts employing additive manufacturing is demonstrated. The design and manufacturing of miniaturised continuous flow oscillatory baffled reactors (mCOBR) employing low cost stereolithography based 3D printing is reported for the first time. Residence time distribution experiments have been employed to demonstrate that these small scale reactors offer improved mixing conditions at a millimetre scale, when compared to tubular reactors. Nearly monodisperse silver nanoparticles have been synthesised employing mCOBR, showing higher temporal stability and superior control over particle size distribution than tubular flow reactors.